Analisis Faktor-Faktor yang Mempengaruhi Konsumsi Mi Instan pada Generasi Muda - Abdillah , Winda; Setyawan, Yuswanto (JURNAL KESEHATAN PRIMER, 2025)
Background:  Instant noodle consumption has become a popular dietary trend among young adults due to its convenience, affordability, and appealing taste. However, frequent intake may contribute to poor nutritional quality and increase long-term health risks. Objectives: To examine the relationship between instant noodle consumption patterns and potential health implications among young adults. Method: A cross-sectional design was applied to 250 respondents using structured questionnaires assessing consumption frequency, portion size, and lifestyle factors. Statistical analyses included chi-square tests and logistic regression to identify significant associations with self-reported health indicators. Results: The results indicated a significant association between high-frequency instant noodle consumption and unhealthy dietary habits, including low intake of fruits and vegetables and higher consumption of sugary drinks (p < 0.05). Spearman correlation showed significant positive relationships between consumption frequency and affordability (ρ = 0.412, p = 0.001), taste preference (ρ = 0.367, p = 0.002), and convenience (ρ = 0.295, p = 0.009), while peer influence was not significant (ρ = 0.158, p = 0.073). Conclusion: The study concludes that frequent consumption of instant noodles is significantly associated with unhealthy dietary patterns among young adults, highlighting the importance of nutrition education, promotion of healthier alternatives, and targeted public health interventions to encourage balanced diets.